Efektivitas Psikoedukasi sebagai Strategi Meningkatkan Pemahaman Bullying pada Remaja Panti Asuhan X di Kota Padang - Juliah, Farhany Vi; Nurmina, Nurmina (MASALIQ, 2024)
Bullying is something that is destructive and has become a phenomenon that is familiar to our ears. One of the factors that influences the level of bullying is the environment and upbringing. Teenagers in orphanages have limited or even no interaction with their parents. They also cannot form a deep relationship with the caregiver, because the caregiver also has divided responsibilities and attention to other children. These conditions are important reasons to increase their understanding of bullying. One way to achieve this is through psychoeducation. This research is quantitative study with a one-group time series design. A sample of 15 people was selected using purposive sampling technique. The results of the study found that there was an increase in understanding of bullying among teenagers at orphanage X after being given psychoeducation.